The Implementation of the (Human Immunodeficiency Virus) / (Acquired Immune Deficiency Syndrome) Prevention Policy at the Kedungwaringin Community Health Center, Kedungwaringin District, Bekasi Regency - Nani Maryani; Yeti Rohayati; Yofy Syarkani (Sean Institute, 2025)
This study aims to analyze the implementation of the HIV/AIDS prevention policy at the Kedungwaringin Community Health Center (Puskesmas), Bekasi Regency, based on the Van Meter and Van Horn policy implementation model, which includes six variables: policy standards and objectives, resources, inter-organizational communication, implementing characteristics, socio-economic-political conditions, and implementers’ disposition. The research employed a descriptive qualitative method, with data collected through in-depth interviews with program managers, health workers, and PLWHA (People Living with HIV/AIDS). The results show that the implementation of the policy has a clear legal basis and standard operating procedures (SOPs), but they are not yet fully understood by all implementers, particularly cadres who have not received further training. Limited human resources, operational funds, and training are the main obstacles to program effectiveness. Vertical communication with the Health Office functions well through the SIHA 2.1 application, but horizontal communication with village authorities, NGOs, and the community remains suboptimal. In addition, social stigma against PLWHA and economic barriers among the community hinder sustainable access to health services. Program implementers’ motivation tends to decline due to high workloads, lack of incentives, and insufficient supervision. In conclusion, the implementation of the HIV/AIDS prevention policy at the Kedungwaringin Community Health Center has been carried out but is not yet optimal. Strengthening human resource capacity, regional budget support, cross-sectoral coordination, and educational and inclusive approaches are needed to reduce stigma and expand service coverage. Support from all stakeholders is essential for the policy to be implemented effectively and sustainably.